Effect of natural colourant and synthetic colourant on pH value of lipstick - Ma, Sze Hui (2014)
Lipstick is one of the cosmetics that are commonly introduced in the market place. As public concern towards the long term effect of synthetic materials used in cosmetic formulations, such as the synthetic colourant, therefore natural ingredients are getting more preferred. In this research, both natural and synthetic coloured lipsticks were produced. Three types of natural colourant extracted from pandan leaves, dragon fruit, and butterfly peas flowers were used as colourant where matching synthetic colourant also been used to produce another set of lipstick for comparison purposes on the pH value of lipstick. The pH of the natural colourants was found to be much neutral in pH compared with that of synthetic. The same results were obtained after incorporated into the lipstick production. The pandan leaves have been identified as the least compatible natural colourant to be used in cosmetic products that require heat treatment. The consumer acceptance was investigated using the Ranking Test (Likert Scale) and Hedonic Scale test. At the end of the investigation, natural red lipstick was being chosen as the best preferred lipstick regarding its colour and pH.